36. KNOWLEDGE AND PRACTICE OF EXCLUSIVE BREASTFEEDING FOR THE FIRST 6 MONTHS AND FACTORS RELATED TO THE PRACTICE AMONG MOTHERS WHO GAVE BIRTH AT DA NANG HOSPITAL FOR WOMEN AND CHILDREN IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: (1) To describe knowledge of breastfeeding and practice of exclusive breastfeeding for the first 6 months among mothers who gave birth at Da Nang hospital for women and children and (2) To analyze some factors related to the practice of exclusive breastfeeding for the first 6 months.Methods: A cross-sectional study was conducted among 230 mothers who gave births at Da Nang hospital for women and children when their children are 6 months of age. Data were collected by direct interviews mothers at households and at Commune Health Stations from February 1, 2023 to April 30, 2023. Data was entered into Excel files and transferring to Epi Info software version 3.5.1 of the US CDC for analysis.Results: The results showed that 66,5% of mothers had good knowledge about breastfeeding. The rate of exclusive breastfeeding for the first 6 months was 56.5%. Among women who exclusive breastfed their children for 6 months, there were 70% practicing all steps of breastfeeding correctly.Mothers who had good knowledge of breastfeeding, breastfeed their babies within the first hour after birth, took maternity leave for 6 months after giving birth, and had the support of their husbands had a higher rate of exclusively breastfeeding practice for 6 months (60,8%, 60,1%, 61,1% and 62,9%, respectively) than the corresponding groups (48.1%; 42.4%; 35.0% and 50.0%, respectively). These differences were statistically significant with OR of 1.68; 2.04; 2.91 and 1.69, respectively and p
Keywords: Breastfeeding, practicing exclusive breastfeeding, postpartum mothers.